(untitled) (NOURA: Jurnal Kajian Gender dan Anak, 2017)
Women empowerment in the field of economy in particular, should be maximized necessary empowerment program for women community both in home industry. The presence of local food products that exist at Desa Kemuja “Pembuatan Beras Aruk” should be followed by the availability of basic ingredients of how high quality cassava. Furthermore, in terms of processing, packaging and branding, and marketing should be more improved in order to really be a support and help the family economy. One type of business currently KPRL “Pembuatan Beras Aruk” in order to foster the public interest in creating employment for all parties specifically for the improvement and empowerment of women’s economy. The existence of this business should be a model of tiered training and more optimized, so that the reliable and professional human resources in turn the production level the better.